2023
DOI: 10.3390/ijms24043237
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitotic Slippage in Creating a “Female Pregnancy-like System” in a Single Polyploid Giant Cancer Cell

Abstract: In our recent work, we observed that triple-negative breast cancer MDA-MB-231 cells respond to doxorubicin (DOX) via “mitotic slippage” (MS), discarding cytosolic damaged DNA during the process that provides their resistance to this genotoxic treatment. We also noted two populations of polyploid giant cells: those budding surviving offspring, versus those reaching huge ploidy by repeated MS and persisting for several weeks. Their separate roles in the recovery from treatment remained unclear. The current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…The small GTPases Cdc42 can regulate the expression of cytoskeletal proteins which are involved in regulating cell polarity, microtubule dynamics, and asymmetric cell division 5 , 27 , 28 . In the present study, we confirmed that Cdc42 and its related proteins in the regulation of cytoskeleton are involved in the asymmetric generation of PGCCs to generate progeny cells with enhanced invasion and migration abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The small GTPases Cdc42 can regulate the expression of cytoskeletal proteins which are involved in regulating cell polarity, microtubule dynamics, and asymmetric cell division 5 , 27 , 28 . In the present study, we confirmed that Cdc42 and its related proteins in the regulation of cytoskeleton are involved in the asymmetric generation of PGCCs to generate progeny cells with enhanced invasion and migration abilities.…”
Section: Discussionmentioning
confidence: 99%
“…With regards the embryonic nature of cancer exhibited by PGCCs as supported by the TCGA database in [13] and previous studies [33,34], the most recent paper in this Issue by Salmina et al [14] added an unexpected aspect to the characteristics of PGCCs. As created by repeated mitotic slippage in a breast cancer cell line in response to doxorubicin treatment, the transcriptome analysis of the resulting PGCCs revealed not only female meiosis but also stark upregulation of the invasive "female pregnancy" Gene Ontology module elaborated in the innate immunity network.…”
mentioning
confidence: 89%
“…Currently, there are several converging and parallel hypotheses of how the cancer genome is regulated. New ideas for therapies and various facets of these hypotheses are explored in the ten articles presented in this Special Issue [5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4A) and in particular the system of embryo invasion and "female pregnancy" (Fig. 4B) [35]. It is pioneered by the AP-1 complex.…”
Section: Phylogenetic Ap-1-related Resistant Response Of Basal Breast...mentioning
confidence: 99%